Evaluating Current Techniques for Detecting Vulnerabilities in Ethereum Smart Contracts - Maddula, Sai Sirisha (Engineering International, 2023)
Ethereum intelligent contract security must be guaranteed since these decentralized apps oversee large-scale financial transactions independently. To strengthen the dependability and credibility of Ethereum smart contracts, this paper assesses existing methods for finding weaknesses in them. The primary goals are to evaluate how well hybrid approaches, formal verification, dynamic analysis, and static analysis find vulnerabilities. Methodologically, a thorough assessment of available resources and instruments was carried out to evaluate the advantages and disadvantages of each approach. Important discoveries show that although static analysis covers a large area, it ignores runtime-specific problems and produces false positives. While highly effective in finding runtime vulnerabilities, dynamic analysis is resource-intensive. High assurance is provided by formal verification, although it is complex and resource-intensive. Hybrid approaches combine several approaches to provide a well-rounded strategy but must be used carefully. The policy implications emphasize that to limit risks effectively, it is crucial to embrace multifaceted security techniques, set explicit norms, and promote easily accessible verification tools. This research advances our knowledge of smart contract security and guides policymakers and developers on securing blockchain applications.
Keywords: Ethereum; Smart contracts; Vulnerability Detection; Security Analysis; Blockchain Technology; Code Auditing; Solidity programming; Risk assessment